An effect of the animal condition after gas stunning on quality of slaughter products from Large White pigs - A. A. Semenova; A. I. Sinichkina; I. V. Kozyrev; T. M. Mittelstein (Теория и практика переработки мяса, 2020)
The aim of the research was to establish an effect of gas stunning of pigs at slaughter on the condition of the internal organs and pork functional-technological characteristics. The experiment was carried out in the conditions of the operating enterprise on 37 Large White pigs. When using 94% concentration in a chamber, only 65% of animals were assessed as normally stunned, 30% of animals did not have cardiac activity and were considered dead, 5% of animals retained sensibility. Assessment of the condition of the internal organs, dynamics of pH changes, comparison of moisture holding capacity and color characteristics did not reveal substantial and statistically significant differences between slaughter products from normally stunned animals and animals died during stunning. The authors discuss mortality of animals before the beginning of bleeding as a possible cause of similar results of investigation of the internal organs and meat quality from animals with and without cardiac activity after gas stunning.